MATHEMATICAL MODELING OF LIGHT PROPAGATION IN OPTICAL FIBERS TAKING INTO ACCOUNT MANDELSTAM-BRILLOUIN SCATTERING - DONSKYI, OLEKSANDR; BARAS, SVIATOSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents a detailed study of the mathematical modeling of light propagation in modern fiber-optic communication lines, taking into account the phenomenon of Mandelstam–Brillouin scattering (SBS), which plays a significant role in the formation of nonlinear effects in optical fibers. Particular attention is paid to the physical mechanisms responsible for the occurrence of this type of scattering, including the interaction of electromagnetic waves with acoustic phonons in the fiber medium, which leads to the appearance of a frequency-shifted backward-propagating wave and changes the spectral and power characteristics of the transmitted signal. The work provides a comprehensive analysis of the impact of SBS on signal quality, such as the increase in noise level, reduction in transmission efficiency, and limitations on the maximum achievable power of optical channels. A set of mathematical models based on coupled differential equations derived from Maxwell’s equations and acoustic wave equations is presented, allowing for a more accurate description of the interaction between the light wave and acoustic vibrations of the medium, as well as the consideration of such parameters as nonlinear gain, acoustic damping, and the effects of external influences. A review of current research and the most relevant approaches to suppressing or controlling SBS in long-distance fiber-optic systems is conducted, including methods based on modulation formats, temperature control, and the use of special fiber structures. Finally, promising directions for further scientific and practical work are identified, including the development of advanced computational models and experimental techniques aimed at optimizing the design of optical communication systems with reduced nonlinear distortions and enhanced reliability.